Social dimensions of preimplantation genetic diagnosis: a literature review. Issue 1 (2nd January 2019) - Lemke, Thomas; Rüppel, Jonas
Abstract : The study provides a systematic overview of research on the social implications of preimplantation genetic diagnosis (PGD). The analysis focuses on empirical studies that provide insights into its heterogeneous fields of application and the concrete experiences of its users. The literature review shows that three areas of concern and controversial topics are particularly relevant for a social-scientific evaluation of PGD. Firstly, we present attitudes towards and assessments of PGD based on an ongoing expansion and transformation of its fields of application. This process includes not only more and more disorders and disease risks but also applications that are not disease-related. Secondly, there is evidence of significant gender asymmetries and financial concerns regarding the use of and access to PGD. Thirdly, the empirical studies point to a shift in normative expectations towards the idea of "genetic reproductive responsibility" and possible discriminatory consequences for individuals and families with diseases and disabilities.